Autophagy facilitates cytokine-induced ICAM-1 expression. Issue 2 (February 2014) - Wang, Chi-Yun; Chiang, Tzu-Hui; Chen, Chia-Ling; Tseng, Po-Chun; Chien, Shun-Yi; Chuang, Yi-Jui; Yang, Tsan-Tzu; Hsieh, Chia-Yuan; Choi, Pui-Ching; Lin, Chiou-Feng
ICAM-1 can be induced by inflammatory cytokines such as IFN-γ and TNF-α. This study investigated whether autophagy regulates ICAM-1 given that autophagy facilitates signaling of these two cytokines. Exogenous IFN-γ induced ICAM-1 in human lung epithelial A549 cells carrying wild type p53, a transcription factor reported for ICAM-1, but not in PC14PE6/AS2 (AS2) cells carrying mutated p53. However, IFN-γ also induced ICAM-1 in A549 cells with short hairpin RNA-silenced p53. No changes in IFN-γ receptor expression were observed in AS2 cells, but IFN-γ-activated Jak2/STAT1/IFN regulatory factor 1 was markedly decreased. In AS2 cells, increased levels of reactive oxygen species induced the activation of Src homology domain-containing phosphatase 2 (SHP2), while SHP2 was essential for IFN-γ resistance. AS2 cells showed autophagy resistance, and the manipulation of the autophagy pathway altered IFN-γ resistance. Aberrant Bcl-2 expression and mammalian target of rapamycin activation contributed to both autophagy resistance and IFN-γ resistance. Autophagy, but not p53, also modulated TNF-α-induced NF-κB activation and ICAM-1 expression. Inhibiting autophagy decreased the adhesion of human monocytic U937 cells to IFN-γ-treated A549 cells. These results demonstrated that IFN-γ and TNF-α induced ICAM-1 expression through a common pathway that was regulated by autophagy, but not p53.